Cardiotocography Properties Mothers with Pregnancy Induced Hypertension - Angulo Cárdenas, David (1998)
OBJECTIVE : To compare the CTG tracings products without mothers Pregnancy Induced Hypertension (PIH) and contrasted with the state of the newborn. MATERIAL AND MÉTOD0S : Cohort study of 6 months in the Perinatal Maternal Institute , reviewing a total of 287 CTG records , of which 116 were discarded . Ninety-six plots were to mothers with PIH and 75 mothers without PIH . Baseline (LB) , variability , accelerations , decelerations , Movements Fetal vibroacoustic stimulation Reactivity : The following parameters were evaluated. RESULTS : The LB was within the normal range in the 95.83 % of hypertensive and 100 % of pregnant control. The RR of variability < 5 beats/min in hypertensive patients was 1.43 (95 % CI) . High risk of doing < 5 min accelerations in 30 products to mothers with PIH was found. No slowdowns type II products HIE mothers evidenced. CONCLUSlONS : The product features cardiotocography mothers with PIH are: LB 120-160 beats/min , variability < 5 beats/min , less than 5 accelerations in 30 min and hypoactivity.